Zero Waste programme – key principles and implementation prospects - Sushkova, A.; Chebotarоva, М.; Chebotarоva, I.; Yatsenko, L. (ТОВ «Друкарня Мадрид», 2023)
The work examines the principles of the Zero Waste programme and the specifics of its implementation in Europe and Ukraine. The programme can be implemented at the level of cities, business structures, as well as in personal life. The work also proves the relevance of using eco-friendly packaging.
Keywords: ecology; Zero Waste programme